Fabrication of omega-shaped microwell arrays for a spheroid culture platform using pins of a commercial CPU to minimize cell loss and crosstalk. (14th August 2018) - Kim, Kideok; Kim, Sung-Hwan; Lee, Gi-Hun; Park, Joong Yull
Abstract: A cell spheroid culture has the benefit of simulating in vivo three-dimensional cell environments. Microwell systems have been developed to mass-produce large quantities of uniform spheroids, and are frequently used in research areas, such as cell biology, anticancer drug development, and regenerative therapy. Recently reported concave-bottomed microwell systems have delivered more benefits in producing spheroids of higher quality and facilitating more effective research. However, microwell fabrication methods are often complicated or expensive, and there are inherent limitations in the functions and characteristics of existing microwells. Therefore, further studies on concave microwell systems are required. In this study, we fabricate spherical microwells with funnel-shaped entrance structures for spheroid culture; the shape is an upside-down omega ( ), and is thus named 'Omega-well'. The Omega-well array is fabricated using the capillary action of liquid polymer on the pins of a computer central processing unit, which is accomplished without requiring expensive materials or difficult procedures. Various characteristic analyses are performed by experiments and computer simulation. It is demonstrated that cell loss is minimized during cell seeding, a produced spheroid does not easily escape, and that crosstalk between microwells is significantly reduced. The novel fabrication method and Omega-well platform proposed in this study are highly practical, and thus will be useful tools in biology and pharmaceutical labs.